A high strength, free-standing cathode constructed by regulating graphitization and the pore structure in nitrogen-doped carbon nanofibers for flexible lithium–sulfur batteries. Issue 15 (3rd April 2017) - Song, Xiong; Wang, Suqing; Bao, Yue; Liu, Guoxue; Sun, Wenping; Ding, Liang-Xin; Liu, Huakun; Wang, Haihui
Abstract : A high strength, flexible cathode was designed for Li–S batteries by introducing graphitic carbon and hierarchical pores in carbon nanofibers. Abstract : We demonstrate here a novel strategy to prepare a flexible and free-standing sulfur cathode with improved mechanical strength, the matrix of which is constructed from graphitized nitrogen-doped mesoporous carbon nanofibers (NPCFs). Benefiting from a unique micro/mesoporous structure and highly graphitic carbon, the NPCF film is capable of accommodating more sulfur, and maintains substantially higher mechanical strength and flexibility after sulfur loading as compared with traditional microporous carbon nanofiber films. As a free-standing and flexible cathode for Li–S batteries, the robust composite film exhibits excellent rate capability (540 mA h g −1 at 5C) and cycling stability (76.5% retention after 500 cycles at 5C).